Nanoparticles and Microparticles of Polymers and Polysaccharides to Administer Fish Vaccines - Spencer-Ossa, E; Sandino-Garcia, A; Rivas-Aravena, A (2013)
Aquaculture has become an important economic sector worldwide, but is faced with an ongoing threat from infectious diseases. Vaccination plays a critical role in protecting commercially raised fish from bacterial, viral and parasitic diseases. However, the production of effective vaccines is limited by the scarcity of knowledge about the immune system of fish. Improving vaccines implies using antigens, adjuvants and employing methods of administration that are more effective and less harmful to the fish. In this context, in recent year there have studies of methods of encapsulating antigens in matrices of different types to apply in fish vaccines. This work reviews the new methods to improve fish vaccines by encapsulating them in polymers and polysaccharides.